British Land Policies in the Gold Coast and Her Relations with Asante - Adu-Gyamfi, Samuel; Bempong, Emmanuel; Yartey, Henry Tettey; Darkwa, Benjamin Dompreh (Studia Historiae Oeconomicae, 2020)
Colonization successfully advanced various reforms in Africa that affected several practices on the continent. The various customs that have been affected include the land tenure system of British colonies in particular. An abundance of laws and policies were adopted with the sole aim of conserving the environment. These policies often clashed with indigenous interests and witnessed counter attacks as a result. Despite this, there is little information in the literature concerning how British land policies shaped their relations with the indigenous people, particularly the Asante. Based on a qualitative research approach, the current study uses Asante as a focal point of discourse in order to historically trace British land policies and how they, the British engaged with the people of Asante. From the discourse, it should be established that the colonial administration passed ordinances to mobilize revenue and not necessarily for the protection of the environment. In addition, the findings indicated that the boom in cash crops, such as cocoa and rubber, prompted Britain to reform the land tenure system. With the land policies, individuals and private organizations could acquire lands from local authorities for the cultivation of cash crops. We conclude that the quest to control land distribution caused the British to further annex Asante.